CHECKLIST OF VASCULAR PLANTS FLORA OF THE “ZALISSIA” NATIONAL NATURE PARK - Kolomiichuk, Vitaliy; Shynder, Oleksander; Baranskyi, Oleksander; Shevera, Myroslav (Biota. Human. Technology, 2024)
The aims of the study. To determine the species composition of the vascular plants flora of the «Zalissya» National Nature Park (Kyiv and Chernihiv Oblasts). Methodology. The research is based on the results of the authors' original research, which was carried out by route on the territory of the «Zalissia» NPP during 2021–2023. In the work also used literature the herbarium material from the National herbarium of Ukraine of the M.G. Kholodny Institute of Botany, NAS of Ukraine (KW), including the A. Rogovich personal collection, herbariums of the M.M. Gryshko National Botanical Garden, NAS of Ukraine (KWHA) and acad. O.V. Fomin Botanical Garden of Taras Shevchenko National University in Kyiv (KWHU), as well as data’s from the iNaturalist database (https://www.inaturalist.org/). Classification of alien species is given by J. Kornaś (1968). The species names are given according to POWO (2024).Scientific novelty. The species composition of the flora of vascular plants of the «Zalissya» National Nature Park, which includes 778 species and subspecies, was established, and an its annotated checklist was complied. Conclusions. It was established that most taxa of the studied flora, namely 612 species and subspecies (78.7%) belong to the natural component. A rather high percentage is a group of alien taxa - 166 species and subspecies (21.3%). In modern flora, its adventitization is increasing due to the high percentage of non-native species. Current tasks include: a) monitoring of the state of the flora, b) search and confirmation of rare species, which were previously mentioned for the territory of the Park (e.g. Astragalus arenarius, Dactylorhiza sambucina, Echium russicum, Lycopodium annotinum, Orchis sambucina, Thesium ebracteatum), c) research on the distribution of alien species, including invasive (e.g. Acer negundo, Amelanchier spicata, Amorpha fruticosa, Cytisus scoparius, Phragmites altissimus, Prunus serotina, Solidago canadensis) and pose a threat to phytodiversity.